2020
DOI: 10.1371/journal.pone.0228803
|View full text |Cite
|
Sign up to set email alerts
|

High body fat percentage and low consumption of dairy products were associated with vitamin D inadequacy among older women in Malaysia

Abstract: Background Serum vitamin D insufficiency is a public health issue, especially among older women. Sun exposure is fundamental in the production of vitamin D, but older women have less optimal sun exposure. Therefore, factors such as body composition and diet become more essential in sustaining sufficient serum levels of vitamin D. The objective of the current study is to determine factors contributing towards serum vitamin D insufficiency among 214 older women. Methods The respondents had their body weight, hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
1
11
0
1
Order By: Relevance
“…Surprisingly, older adults (M-HEI score: 70.2 ± 12.0) had significantly better diet quality than the younger age group (59.7 ± 9.9) [ 44 ]. This finding appears to be consistent with a recent study reporting an M-HEI score of 66.9 ± 9.9 in women above 50 [ 48 ]. Nohan et al [ 49 ] also reported that almost 75% of the older adults in their study had good diet quality.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Surprisingly, older adults (M-HEI score: 70.2 ± 12.0) had significantly better diet quality than the younger age group (59.7 ± 9.9) [ 44 ]. This finding appears to be consistent with a recent study reporting an M-HEI score of 66.9 ± 9.9 in women above 50 [ 48 ]. Nohan et al [ 49 ] also reported that almost 75% of the older adults in their study had good diet quality.…”
Section: Resultssupporting
confidence: 93%
“…These studies also tended to focus more on sociodemographic factors affecting food insecurity and the association of diet quality indices with nutritional status. Studies using the HEI or DQI or their modified versions tended to be more in the urban [ 39 , 44 , 45 , 46 , 48 , 49 , 63 , 66 ] and clinical settings [ 54 , 60 , 61 , 62 , 64 , 65 ]. The latter were also more likely to focus on the association of diet quality with cardiometabolic or chronic disease risks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major community-based survey and a number of selected sample studies were conducted in Malaysia to determine vitamin D status among the people. From 2004 to 2020, there were published studies of vitamin D status involving adult men and women [ 8 , 11 , 12 , 13 , 14 , 15 , 16 ], pregnant women [ 17 , 18 , 19 ], postmenopausal women [ 20 , 21 ], adolescents [ 7 , 22 ], children [ 23 , 24 ], and also children with specific diseases such as spina bifida [ 25 ], epilepsy [ 26 , 27 ], chronic liver disease [ 28 ], and atopic dermatitis [ 29 ]. The majority of the research was conducted in Peninsular Malaysia, specifically in Kuala Lumpur and tertiary hospitals.…”
Section: Epidemiology Of Vitamin D Deficiencymentioning
confidence: 99%
“…The relationship between vitamin D concentration and diet was focused on many studies [ 18 , 19 , 20 , 21 , 22 ]. However, very few data exist on the plasma vitamin D concentration in people on the low-carbohydrate-high-fat diet [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%